Independent Curriculum and SPMI: Two Pillars Driving the Progress of SMPN 15 Mataram City - Dewi Ratna Hidayati; Deni Saputra; Mohamad Mustari (Penerbit Hellow Pustaka, 2025)
This research aims to deeply analyze the role of the implementation of the Merdeka Curriculum and the application of the Internal Quality Assurance System (SPMI) as key pillars driving progress at SMPN 15 Mataram City. The school faces challenges in improving the quality of education to be relevant to 21st-century needs. A qualitative approach with a case study method was used to understand this phenomenon holistically and contextually. Data collection involved in-depth interviews with the principal and the curriculum vice principal, Ms. G. Ayu S. Astuti, observation of teaching and learning activities and quality assurance meetings, as well as analysis of documents related to the Merdeka Curriculum and the SPMI cycle. The findings indicate that the integration of the Merdeka Curriculum and SPMI has created a significant positive synergy. The Merdeka Curriculum provides flexibility and encourages student-centered learning innovation, while SPMI ensures that these innovations are planned, measurable, andsustainable through the planning, implementation, evaluation, control, and improvement (PPEM) cycle. The Merdeka Curriculum's implementation has successfully enhanced student competencies in Pancasila student profile reinforcement projects (P5) and enriched formative assessment. Meanwhile, the SPMI cycle, particularly in the evaluation and control stages, plays a crucial role in identifying areas for Merdeka Curriculum improvement and formulating effective follow-up actions. The conclusion of this study confirms that the Merdeka Curriculum and SPMI are not just programs, but are two fundamental pillars supporting a culture of quality and driving educational transformation at SMPN 15 Mataram City. Furthermore, SMPN 15 Mataram City faces a challenge in implementing the Merdeka Curriculum Based on Deep Learning, specifically that a few teachers have not yet been able to fully transition from the previous curriculum. However, the percentage of these teachers is very small, only about 3–4 individuals, equivalent to 5% of the majority of teachers, 90%, who are adaptable and capable of implementing the Merdeka Curriculum optimally. Such a minor challenge does not prevent SMPN 15 Mataram City from maintaining its status as a superior, favorite, quality, and competitive school.